Quantitation of Phenolic Benzotriazole Class Compounds in Plasma by Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS). (2nd September 2022) - Mutlu, Esra; South, Natalie; Pierfelice, Jessica; Djonabaye, Alison; Pauff, Mindy; Burback, Brian; Waidyanatha, Suramya
Abstract: Phenolic benzotriazoles are used as ultraviolet stabilizers in consumer products and have been detected in the environment suggesting potential human exposure. Phenolic benzotriazoles were nominated to the Division of National Toxicology Program for testing based on their potential widespread human exposure and lack of adequate toxicity data. Nine chemicals were selected for toxicological evaluation, representing unsubstituted (2-(2H-benzotriazole-2-yl)phenol, (P-BZT)), monosubstituted (drometrizole; 2-(2H-benzotriazol-2-yl)-4-tert-butylphenol (tBu-BZT); octrizole), disubstituted (2-(2H-benzotriazol-2-yl)-4, 6-bis(1-methyl-1-phenylethyl)phenol (diMeEtPh-BZT), 2-(2H-benzotriazol-2-yl)-4, 6-bis(1, 1-dimethylpropyl)phenol (ditPe-BZT); 3-(2H-benzotriazol-2-yl)-5-(1, 1-dimethylethyl)-4-hydroxybenzenepropanoic acid, octylester (tBuPrOcEst-BZT) and halogenated trisubstituted (bumetrizole; 2-(5-chloro-2H-benzotriazol-2-yl)-4, 6-bis(1, 1-dimethylethyl)phenol (ditBuCl-BZT)) compounds. Different extraction methods were utilized and methods were developed to determine phenolic benzotriazoles by quantitating free (unconjugated parent) and total (free and conjugated parent) analytes in plasma of rats to aid in interpretation of toxicity data, understanding of absorption, distribution, metabolism, and excretion differences. The calibration standard range was from 1 to 500 ng/mL for free analytes and 1 to 1000 ng/mL for total analytes. The methods were linear (r 2 ≥ 0.99). The accuracy was determined as the relative error (RE) and ranged from −18.2 to +17.8, and precision as the relative standard deviation (RSD) and ranged from 0.0 to 20.1% for both free and total plasma calibration standards, respectively. The limits of quantitation were ≤5.0 and 10.0 ng/mL and limit of detection ≤ 1.2 and 2.0 ng/mL, for free and total analytes, respectively. These results demonstrate that the methods are suitable for quantitation of free and total analytes in rat plasma.